Traditional Knowledge And Ethnobotanical Utilization of Edible Plants In The Repong Damar Agroforestry System, Bengkunat Subdistrict, Pesisir Barat Regency, Lampung, Indonesia - Lathifa Hanun, Salwa; Hari Kaskoyo; Sugeng P. Harianto; Duryat (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Ethnobotany explores the interrelationship between humans and plants utilized in daily life, particularly as sources of food. This study describes the traditional knowledge of local communities in utilizing the biodiversity of edible plants within the Repong Damar agroforestry system in Bengkunat Subdistrict, Pesisir Barat Regency, Lampung, Indonesia. An ethnographic approach was applied through semi-structured interviews, field observations, and participatory documentation with local farmers to collect detailed information on plant species, processing methods, and patterns of utilization. The findings show that the community continues to utilize a wide variety of plants, both cultivated and naturally growing within the repong, as essential food sources. Edible fruits include Durian (Durio zibethinus), Duku (Lansium domesticum), Mango (Mangifera indica), Water Apple (Syzygium aqueum), Jackfruit (Artocarpus heterophyllus), Mangosteen (Garcinia mangostana), Soursop (Annona muricata), Passion Fruit (Passiflora edulis), and Papaya (Carica papaya). Other species such as bitter bean Petai (Parkia speciosa), Jengkol (Archidendron pauciflorum), Jaling (Archidendron bubalinum), Melinjo (Gnetum gnemon), and Taro (Litsia sp.) are prepared as traditional side dishes. In addition, Indonesian bay leaf (Syzygium polyanthum), Torch Ginger (Etlingera elatior), Turmeric (Curcuma longa), and Black Pepper (Piper nigrum) are used as natural seasonings, While Sugar Palm (Arenga pinnata) and Coffee (Coffea arabica) serve as raw materials for beverages and processed local products. The diversity of edible plants in Repong Damar highlights its significant role not only as a resin-producing landscape but also as a rich reservoir of natural food resources that sustains local nutrition, strengthens community food security, and preserves traditional ecological knowledge that continues to be transmitted across generations within the coastal communities of Lampung.